2022
DOI: 10.1186/s12891-022-05232-w
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in shoulder performance fatiguability are affected by arm position, dominance and muscle group

Abstract: Background Injury prevalence data, muscle strength, and fatiguability differ between males and females. In addition, arm spatial orientation affects muscle activation and strength of the shoulder muscles. Nevertheless, little research has been conducted in relation to the shoulder rotator muscles comparing men and women. Therefore, the main aim of of this study was to perform a comparative investigation between two arm spatial orientations (45° and 90° of abduction in the frontal plane) during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
(66 reference statements)
0
0
1
Order By: Relevance
“…Horobeanu et al concluded in their study that the performance values of shoulder rotator muscles in males were about 50% higher than in females [28]. However, our findings are not in line with this study as despite more number of males in Group 1 (smartphone addicts), the scapular muscle endurance values were found to be lesser in that group as compared to Group 2 (smartphone non -addicts), probably the cause being smartphone addiction.…”
Section: Discussioncontrasting
confidence: 97%
“…Horobeanu et al concluded in their study that the performance values of shoulder rotator muscles in males were about 50% higher than in females [28]. However, our findings are not in line with this study as despite more number of males in Group 1 (smartphone addicts), the scapular muscle endurance values were found to be lesser in that group as compared to Group 2 (smartphone non -addicts), probably the cause being smartphone addiction.…”
Section: Discussioncontrasting
confidence: 97%